1968
DOI: 10.4319/lo.1968.13.2.0293
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Observations on Coral Reef Plankton1

Abstract: ABSTBRCTPlankton collections near coral reefs were made by hand-towing nets while swimming and by using a suction device for sampling caves. Plankton in sheltered areas was considcrably different from that in nonsheltered areas; some plankton forms maintained position near coral reefs, indicating that the terms planktonic and epibenthic may represent extremes of a behavior continuum.Copepods were observed to swarm and mysids to school on the reef. Mysids ancl nesting pomacentricls exhibit a loosely developed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
120
0
4

Year Published

1970
1970
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(127 citation statements)
references
References 2 publications
3
120
0
4
Order By: Relevance
“…Johanncs (1967) found that Arte-W&Z nauplii kept in tanks containing coral mucus grew faster and lived longer than those in control tanks. Perhaps the occurrcnce of dense concentrations of zoopIankton near the coral reef, noticed by Emery ( 1968) and more recently by Tranter and George ( 1969) at Kavaratti during October 1968, may be due to the presence of large quantities of particulate matter as a readily available food. The particulate production in corals thus becomes an intercsting adaptation, providing a potential source of energy to the zooplankton and thus providing a partial cncrgy return to the corals as they feed on the plankton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johanncs (1967) found that Arte-W&Z nauplii kept in tanks containing coral mucus grew faster and lived longer than those in control tanks. Perhaps the occurrcnce of dense concentrations of zoopIankton near the coral reef, noticed by Emery ( 1968) and more recently by Tranter and George ( 1969) at Kavaratti during October 1968, may be due to the presence of large quantities of particulate matter as a readily available food. The particulate production in corals thus becomes an intercsting adaptation, providing a potential source of energy to the zooplankton and thus providing a partial cncrgy return to the corals as they feed on the plankton.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have found large quantities of zooplankton (Russell 1934;Emery 1968), while others have reporte,d extremely lo'w concentrations (Sargent and Austin 1954;Odum and Odum 1955). If large conccntrations of zooplankton do exist, what would be the source of their energy in such coral reef waters of impoverished phytoplankton content?…”
Section: Discussionmentioning
confidence: 99%
“…pelagic throughout their life) include representatives also known to inhabit coral reef environments and behave like typical reef zooplankton. Taxa with such high behavioral flexibility include members of the genera Acartia Dana, 1846, and Oithona Baird, 1843 (Emery 1968;Heidelberg et al 2004;Alvarez-Cadena et al 2014). For neustonic copepods, living in the top 5-10 cm of the sea surface, such behavioral plasticity is so far unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Copepod densities in swarms ranging from 0.10 to 3.32 copepods ml"' have been reported for fine (1 cm-1 m) and micro (10-100 m) space scales (Emery, 1968;Hamner and Carleton, 1979;Ueda et al, 1983). These swarms are composed predominantly of adults and copepodids but not nauplii (Hamner and Carleton, 1979;Ueda el al., 1983).…”
Section: * Introductionmentioning
confidence: 99%
“…Numerous species of calanoid genera Acartia, Centropages, Tortanus and Ridgewayia form swarms (see Emery, 1968;Yeatman, 1969;Humes and Smith, 1974;Hamner and Carleton, 1979;Ueda et al, 1983;Tanaka et al, 1987a;Kimoto et al, 1988). Three cyclopoid copepod species also aggregate in swarms, Oithona nana, Oithona davisae and Dioithona oculata (Emery, 1968;Hamner and Carleton, 1979;Omori and Hamner, 1982;Ueda etal., 1983;Kimoto et al, 1988;Hirota, 1990). Labidocera pavo is the only copepod species reported to form 'schools' (Omori and Hamner, 1982).…”
Section: * Introductionmentioning
confidence: 99%